Zirconia doped with La Fe synthesized by sol gel, used in the trichloroethylene catalytic combustion - Rivera de la Rosa, Javier; Hernández, Araceli; Ledezma Sánchez, Juan José; Rojas, Fernando; Goller, Gülteking
Zirconia is one of the most studied ceramic materials due to its outstanding thermal, mechanical and chemical stability; in addition, acidic, basic, oxidizing and reducing surface properties make this oxide suitable for many catalytic processes [1-3]. Depending on the preparation method and thermal treatment, monoclinic, tetragonal, cubic, or a mixture of these phases can be obtained. The sol-gel method has attracted considerable attention for the preparation of metallic catalysts, since the constituents are mixed in an atomic scale and this generates a uniform distribution of active metals upon the support [4]. The crystalline phase obtained by the sol-gel method can strongly depend on the starting metallic precursor.